Is corporate internet banking really secure? A case study of Hong Leong Bank Berhad / Nur Munirah Mohd So’ud - Mohd So’ud, Nur Munirah (2014)
In the age of internet banking, security level provided by banks is the main concerns. Banks are highly regulated institution and governed by Financial Service Act 2013 (FSA) and Islamic Financial Service Act 2013 (IFSA). Therefore, all implementation taken by banks will endorse by Bank Negara Malaysia. The aim of this study is (i) to find out if Hong Leong Bank Berhad adopts an online business platform, (ii) to identify the challenges faced by Hong Leong Bank Berhad in continuously upgrading its online business platform; (iii) to determine whether the levels of knowledge and experience required by Hong Leong Bank’s staff are adequate enough to successfully meet the expectations of corporate customers in the implementation of Hong Leong online business platform; (iv) to discover the current fraud deterrence features built into Hong Leong online business platform in order to reduce the risk of fraud and misappropriation; and (v) to determine whether the present fraud deterrence features in Hong Leong online business platform are effective enough given today’s development in online banking. This study is based on primary and secondary data from the Hong Leong Bank Berhad as well as the relevant academic journal. The data cover all corporate internets banking handled by the branch operation in Central Five Region in the year 2014. Altogether there were 50 questionnaire distributed branch operation staffs. The study showed that Hong Leong Bank have a platform for corporate customer called Hong Leong Online Business. The aim of this is to fulfil the requirements of the research objectives.